Biodefense Implications of New-World Hantaviruses - D’Souza, Michael Hilary; Patel, Trushar R. (Frontiers in Bioengineering and Biotechnology, 2020)
Hantaviruses, part of the Bunyaviridae family, are a genus of negative-sense, single-stranded RNA viruses that cause two major diseases: New-World Hantavirus Cardiopulmonary Syndrome and Old-World Hemorrhagic Fever with Renal Syndrome. Hantaviruses generally are found worldwide with each disease corresponding to their respective hemispheres. They spread by specific rodent-host reservoirs and are categorized as emerging viruses that pose a threat to global health and security due to their high mortality rate and ease of transmission. Incidentally, reports of Hantavirus categorization as a bioweapon are often contradicted as both US National Institute of Allergy and Infectious Diseases and the Centers for Disease Control and Prevention refer to them as Category A and C bioagents respectively, each retaining qualitative levels of importance and severity. Concerns of Hantavirus being engineered into a novel bioagent has been thwarted by Hantaviruses being difficult to culture, isolate, and purify limiting its ability to be weaponized. However, the natural properties of Hantaviruses pose a threat that can be exploited by conventional and unconventional forces. This review seeks to clarify the categorization of Hantaviruses as a bioweapon, whilst defining the practicality of employing New-World Hantaviruses and their effect on armies, infrastructure, and civilian targets.